Strategi guru dalam membangun karakter nasionalisme pada generasi milenial di era digital - Widiatmaka, Pipit (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2022)
This study aims to describe and analyze the challenges of teachers in building the nationalism character in the millennial generation in the digital era and strategies faced by teachers in building the nationalism character of students in formal education in the digital era. This study uses a qualitative approach using library research methods. Data collection technique with document study, and data analysis used is content analysis. The results of the study indicate that the challenges of teachers in Indonesia in building the nationalism character of the millennial generation are that they have not mastered competencies as educators (pedagogic, professional, social, and personality) to the maximum and have not been able to implement various learning methods and have not been optimal in utilizing digital-based learning media. The teacher's strategy in building the nationalism character of the millennial generation in the digital era is that the teacher must be able to master competencies as an educator, prepare effective learning tools, and implement various learning methods to utilize digital-based learning media. The development of technology is a challenge for teachers in building the nationalism character, so teachers must be able to adapt to the times and always improve their competence.